👤
Lili003
a fost răspuns

7 ( x + 2) + ( x - 1 )(x + 2 ) - 4 = ( x + 2 )(x - 2 ) + 5 ( x + 3 )

Răspuns :

7x+14+x2+2x-x-2-4=x2-2x+2x-4+5x+15                                                                7x+2x-x+2x-2x-5x+x2-x2=15-4+2+4                                                                    3x=17                                                                                                                 x=17÷3                                                                                                                x=5,6